The problem of berst influence on the generalized automatic neuron - E. V. Konovalov (Моделирование и анализ информационных систем, 2007)
A new model of the neuron cell - the generalized automatic neuron (GAN) is considered. This model has an universal character. It combines properties of neuron-oscillator and neuron-detector. The problem of berst influence on the generalized automatic neuron is raised and solved.